Efisiensi Termal Cross Section Double Drum Water Tube Boiler Pengaruh Rasio Udara Bahan Bakar Solar Berbasis Water Level Control (AM61-F) Pada Produksi Saturated Steam Proses Kontinyu - Tiesyah Mainur Aini; Tahdid; Isnandar Yunanto; Erlinawati (Proklamasi 45 University, 2024)
A Boiler is a type of closed vessel that transfers heat energy from the combustion process to water until it becomes hot steam (steam). To produce good steam, the Boiler must be reliable in its heat transfer system, mass transfer system and hydrodynamic system. This will also have an impact on cost, thermal efficiency and the environment. In order to produce steam, good combustion and proper water level regulation are required. Combustion is an exothermic reaction that takes place very quickly, which releases energy in the form of heat and flame and is able to spread heat through a medium. In order for combustion to occur optimally, it must pay attention to the value of the Air Fuel Ratio (AFR). The regulation of the water level also affects the steam produced. This study studies the variables of air fuel ratios (Air Fuel Ratio) 16, 18, 20, 22 and 24 as well as water level levels of 20%, 30%, 40%, 50% and 60%. From this study, a flame temperature value of 685.9°C was obtained with a thermal efficiency of 69,61% Specific Fuel Consumption 0,0000339 kg/kJ which is in the 4th experiment, namely Air Fuel Ratio 22 and Water Level 50% with optimal combustion and steam production results. Keywords: Boiler, Saturated Steam, Air Fuel Ratio, Water Level, Energy, Thermal Efficiency, Specific Fuel Consumption.